Sistem Pemantau Detak Jantung dan Saturasi Oksigen dalam Darah (SpO2) Berbasis IoT - Muhammad Taufiq Tamam; Itmi Hidayat Kurniawan; Anis Kusumawati (Universitas Muhammadiyah Purwokerto, 2023)
Heart rate and blood oxygen saturation (SpO2) are the two main parameters needed to determine the condition of a patient being treated in the intensive care unit (ICU) at a hospital. These two parameters must not be left unattended from monitoring because they can be fatal for the patient.This study aims to create an IoT-based heart rate monitoring and blood oxygen saturation (SpO2) application so that it can be accessed online in real time anytime and anywhere. The observation process is in the form of analog signal changes which are processed with fast fourier transform arithmetic as digital signal processing. The final process of processing displays the measured heart rate and blood oxygen saturation (SpO2).Based on the trial results, the use of the thingspeak platform can work well. Parameters of heart rate and blood oxygen saturation (SpO2) can be accessed online in real time anytime and anywhere so as to assist medical personnel in monitoring patients in hospitals.